Evaluation of undehydrated barley feed fractions and dried oat feed fractions from integrated starch-ethanol process in diets of growing pigs - Näsi, Matti; Aimonen, Erkki (Agricultural Research Centre of Finland, 1992)
Tutkimuksessa selvitettiin yhdistetystä tärkkelys-etanolituotannosta saatavan kuivaamattoman ohravalkuisrehun, ohravalkuis-ohrarehuseoksen ja tärkkelysrankin sekä kuivatun ohrarehun, kauravalkuisrehun ja kaurakuidun rehuarvoa lihasikojen ruokinnassa. Tuoreet rehujakeet oli säilötty natriumbentsoaatilla, 2 g/kg. Rehujakeiden ravintoaineiden sulavuutta ja valkuaisen hyväksikäyttöä tutkittiin neljässä sikojen sulavuus- ja typpitasekokeessa. Rehujakeista analysoitiin normaalien koostumusmääritysten lisäksi myös aminohappojen ja rasvahappojen pitoisuudet. Ohravalkuisrehun valkuisen sulavuus oli korkeampi kuin tärkkelysrankin ja samoin sikojen typen pidättyminen oli ohra-ohravalkuisrehudieetillä korkeampi kuin ohratärkkelysrankkidieetillä. Kauravalkuisrehun sulavuus oli korkea. Ohrarehun ravintoaineiden sulavuus oli alempi kuin kaurakuidun. Ohrarehulisäys alensi dieetin valkuisen sulavuutta ja hyväksikäyttöä. Proteiinipitoisten rehujakeiden energia-arvot olivat korkeita, 1.26-1.60 RY/kg KA, kun taas kuitupitoisten jakeiden olivat huomattavasti alempia.

The nutrient digestibility and protein utilization of undehydrated barley fractions: protein (BP), protein fibre mixture (BPF) and distillers solids (DS) at two levels of inclusion in diets fortified to equal lysine content were assayed with growing pigs in a 6 x 6 Latin square. Dried barley fibre (BF), oat protein (OP) and oat fibre (OF) from integrated starch-ethanol production were evaluated as feed ingredients for pigs in three other trials. DS and OP had a higher essential amino acids content than BP, especially with respect to lysine. All fractions had a rather high ether extract content 46-196 g/kg and their fatty acid composition is presented. BP showed higher protein digestibility than DS (0.931 vs. 0.857) and pigs on BP-diet retained more N than on DS-diet. BF showed a low digestibility of OM and CP and 0.1 inclusion of BF mixed with BP depressed CP digestibility and N-retention. A higher protein supply from cereal protein in the diet promoted N-retention but decreased protein utilization. OP had high digestibility and OF was more digestible than BF. The study confirmed the high digestibility and energy values of the proteinous grain fractions and a high protein utilization when adequately fortified with lysine. The fibrous fractions have a rather low nutrient digestibility and their use in pig diets is therefore limited.
Keywords: Ko; sika; ohra; kaura; rehut; ruokinta; sivutuotteet; cereal protein; digestibility; protein utilization; nitrogen balance; pig feeding